2020
DOI: 10.1186/s12979-020-00190-0
|View full text |Cite
|
Sign up to set email alerts
|

IL-15 deficiency alleviates steroid-induced osteonecrosis of the femoral head by impact osteoclasts via RANKL-RANK-OPG system

Abstract: Background Whether IL-15 is involved in the development of steroid-induced osteonecrosis of the femoral head (ONFH) is investigated. Methods C57BL/6 J and l15−/−mice were injected with methylprednisolone to induce wide type osteonecrosis (WT ON) and IL-15 deficiency osteonecrosis (IL-15−/− ON). Hematoxylin-Eosin (H&E) staining and micro-computed tomography (micro-CT) scanning was used to detect the microstructure. The differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…The previous studies have demonstrated that steroid is an established risk factor of osteonecrosis of the femoral head (ONFH) [4][5][6] . Moreover, numerous researches have proved that the mechanism of steroid-induced osteonecrosis of the femoral head (SONFH) including oxidative stress 7 , osteoclasts activation 8 , bone formation and resorption 9 , et al SONFH most have been diagnosed by magnetic resonance imaging (MRI) 5 . However, the reliable biomarkers of SONFH remained unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies have demonstrated that steroid is an established risk factor of osteonecrosis of the femoral head (ONFH) [4][5][6] . Moreover, numerous researches have proved that the mechanism of steroid-induced osteonecrosis of the femoral head (SONFH) including oxidative stress 7 , osteoclasts activation 8 , bone formation and resorption 9 , et al SONFH most have been diagnosed by magnetic resonance imaging (MRI) 5 . However, the reliable biomarkers of SONFH remained unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, long-term or excess application of glucocorticoids functions as an activator for inflammation. The elevation of proinflammatory cytokines has been found in a mouse model of SIONFH [ 10 , 31 ]. Similar results were found in the rat model of SIONFH in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology and pathological process of SONFH are complex. Oxidative stress [1] , osteoclasts activation [4] , and bone-metabolism disorder [5] have been correlated with SONFH. However, the exact molecular mechanisms of SONFH remain unclear.…”
Section: Introductionmentioning
confidence: 99%